2020
DOI: 10.47626/1679-4435-2020-562
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of Brazilian industrial workers: a review article

Abstract: Workers in general have their quality of life affected; however, in the industrial setting, they are exposed to poor and unhealthy conditions in their workplaces and to different occupational hazards depending on their role, sector of activity, and climatic conditions. This study aimed to analyze the quality of life of Brazilian industrial workers. This is an integrative review. The PICo strategy was used to prepare the research question, and each letter represents one component of the question - population (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Few studies assessing the quality of life of industrial workers, especially in relation to noise, were found. The reviewed studies consistently demonstrate that quality of life deficits among industrial workers are closely tied to multiple dimensions, including vitality, physical functioning, general health, environment, and psychological well-being (Santos et al, 2020). This highlights the intricate interplay between the work environment and employees' overall quality of life.…”
Section: Discussionmentioning
confidence: 96%
“…Few studies assessing the quality of life of industrial workers, especially in relation to noise, were found. The reviewed studies consistently demonstrate that quality of life deficits among industrial workers are closely tied to multiple dimensions, including vitality, physical functioning, general health, environment, and psychological well-being (Santos et al, 2020). This highlights the intricate interplay between the work environment and employees' overall quality of life.…”
Section: Discussionmentioning
confidence: 96%
“…Health-related quality of life (HRQoL) is an important aspect in occupational health as it is linked to an individual’s health as well as his/her personal satisfaction. [ 9 10 ] Different studies have been done to determine evidence of WRMSDs and HRQoL in various industries. [ 1 2 3 4 5 6 7 8 ] However, corrugated box-making industry has remained unobserved for many years in spite of the fact that with the increasing demand for E-Commerce, the use of corrugated boxes has increased substantially.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analyzing their QoL is also vital as it allows their employers to implement methods to improve their QoL in order to improve their performance and productivity. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…We are missing solid evidence from young people entering the workforce. Noise exposure at work is one of the risk factors for a poorer quality of life [ 23 ]. Occupational noise annoyance has been significantly related to mental health, including depressive symptoms and suicidal ideation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%